2016
DOI: 10.1111/sltb.12243
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Firearm Availability and Gun Regulation on State Suicide Rates

Abstract: Past studies on suicide have investigated the association of firearm ownership and suicide risk in the United States. The aim of the present study was to build on previous work by examining the impact of firearm storage practices and the strictness of firearm regulation on suicide rates at the state level. Data were compiled from primarily three sources. Suicide and firearm ownership information was obtained from the Centers for Disease Control and Prevention. Strictness of handgun regulation was derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…The purchase of a gun is also associated with increased risk for death by suicide across all methods—not simply suicide by firearm (Wintemute, Parham, Beaumont, Wright, & Drake, ). These points have been replicated repeatedly, including a recent study by Kposowa, Hamilton, and Wang (), which found that increased gun ownership and unsafe gun storage (particularly guns kept both loaded and unlocked) were associated with significantly elevated statewide suicide rates, even after accounting for a range of potential confounding variables.…”
Section: Descriptive Statistics and Correlationsmentioning
confidence: 80%
“…The purchase of a gun is also associated with increased risk for death by suicide across all methods—not simply suicide by firearm (Wintemute, Parham, Beaumont, Wright, & Drake, ). These points have been replicated repeatedly, including a recent study by Kposowa, Hamilton, and Wang (), which found that increased gun ownership and unsafe gun storage (particularly guns kept both loaded and unlocked) were associated with significantly elevated statewide suicide rates, even after accounting for a range of potential confounding variables.…”
Section: Descriptive Statistics and Correlationsmentioning
confidence: 80%
“…Moreover, "persons with a gun in the home were [are] more likely than others to use a gun to [die by] suicide and less likely than others to [die by] suicide by means of drug overdose, hanging, or other method other than a gun" [85]. Population (household) rates of gun ownership are strongly associated with overall suicide rates, gun suicide rates, and percentage of suicides by gun in the US ( Table 3 and Figure 3) [89][90][91], even when prescription rates of antidepressants are considered [92]. Evidence suggests that 33%-80% of suicidal acts are impulsive [93], and among individuals making nearlethal suicide attempts, 70% of those made the decision within an hour of the attempt, and 24%…”
Section: Is Increased or Unsafe (Disparate) Access To Firearms A mentioning
confidence: 99%
“…We approach this topic from purely a public health perspective. Based upon the preponderance of evidence we wish to emphasize the point, as others have, that reducing access to lethal means will almost certainly save many lives that might otherwise be lost to suicide [67,90,91,95,106,111]. Reducing access to lethal means as involves firearms in particular can take many forms, ranging from individual to community to legislative initiatives.…”
Section: Identifying the Most Effective Firearm Safety Measuresmentioning
confidence: 99%
“…The most commonly cited reason why higher gun prevalence would affect the total number of suicides, and not just the share committed with firearms, is the purportedly greater lethality of shooting attempts compared with that of methods likely to be substituted for shooting (e.g., Kubrin and Wadsworth, ; Kposowa, Hamilton, and Wang, ). National data, however, indicate that the incident fatality rates of shooting suicide attempts are not significantly higher than attempts by hanging, the second‐most common method of suicide in the United States (Kleck, ).…”
mentioning
confidence: 99%